2021
DOI: 10.3389/fphys.2021.742338
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Arterial Stiffness and Muscle Indices Among Healthy Subjects and Subjects With Cardiovascular Risk Factors: An Evidence-Based Review

Abstract: Skeletal muscle is one of the major tissues in the body and is important for performing daily physical activity. Previous studies suggest that vascular dysfunction contributes to reduced skeletal muscle mass. However, the association between vascular dysfunction and muscle mass, muscle strength and muscle flexibility are less established. Therefore, the focus of this review was to investigate the association between arterial stiffness (AS) which is a marker of vascular function, and muscle indices among health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
0
8
2
Order By: Relevance
“…Further, the VAI was associated with chronic inflammation and insulin resistance, due to increases in free fatty acids, interleukin-6, tumor necrosis factor-α, and decreased adiponectin production, related to VAT (23). Inflammatory cytokines and reactive oxygen species lead to decreased nitric oxide concentrations, which are associated with a higher risk of arterial stiffness (24)(25)(26)(27). Additionally, large quantities of fatty acids, due to accumulative visceral adiposity and chronic inflammation, can promote the likelihood of insulin resistance, which is associated with atherosclerosis (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the VAI was associated with chronic inflammation and insulin resistance, due to increases in free fatty acids, interleukin-6, tumor necrosis factor-α, and decreased adiponectin production, related to VAT (23). Inflammatory cytokines and reactive oxygen species lead to decreased nitric oxide concentrations, which are associated with a higher risk of arterial stiffness (24)(25)(26)(27). Additionally, large quantities of fatty acids, due to accumulative visceral adiposity and chronic inflammation, can promote the likelihood of insulin resistance, which is associated with atherosclerosis (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies proposed that reduced blood flow with aging might contribute to the development of sarcopenia. 11 , 12 , 29 , 30 , 31 Reduced blood flow with aging impaired the delivery of oxygen and nutrients to skeletal muscle, which could accelerate the loss of muscle mass and strength. Vascular dysfunction and decreased capillarity were key factors that restrict blood flow and muscle perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular dysfunction and decreased capillarity were key factors that restrict blood flow and muscle perfusion. 11 , 12 , 30 , 31 Population‐based studies had observed that flexibility was associated with vascular dysfunction, 32 , 33 and human trials reported that increasing flexibility enhanced blood flow and capillary growth in skeletal muscle and improved vascular function. 9 , 10 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 Animal‐based studies also found that muscle stretching enhanced blood flow, improved vessel function and induced capillarization of aged skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular exercise training is an effective non-pharmacological therapy to control hypertension ( Pescatello et al, 2015 ; Whelton et al, 2018 ; Williams et al, 20182018 ; Unger et al, 2020 ; Barroso et al, 2021 ) and is able to attenuate pathological cardiac remodeling ( Cattadori et al, 2018 ) and to improve arterial stiffness ( Lopes et al, 2021 ) in hypertensive humans. Combined exercise training, which consists of aerobic and resistance exercise on alternate days, has been associated with better responses in controlling cardiovascular risk factors for cardiovascular diseases ( Figueroa et al, 2011 ; Ho et al, 2012 ; Schroeder et al, 2019 ; Dias et al, 2020a ; Aminuddin et al, 2021 ). However, the impact of combined exercise training on arterial stiffness and cardiac remodeling in SHR are still unclear.…”
Section: Introductionmentioning
confidence: 99%